PEMILIHAN SUPPLIER KEMASAN DUS MENGGUNAKAN FUZZY ANP DAN TOPSIS - Dian Gita Pratiwi (2020)
Supplier selection is immensely critical due to supplier playing a core role in ensuring the availability of raw materials and products needed by the company in the production process. These are certainly imperative factors to keep the competitiveness of any organisation. One organization that currently is experiencing a lack of packaging boxes, which essentially carries the final product, is PT. X, a company that produces wafer. This dependency on a supplier of packaging leads to the urgency of a permanent supplier which has to meet the company's desired criteria and objective calculations. Furthermore, Fuzzy ANP and TOPSIS are examples of decision-making methods that can be used as a structural guidance for supplier selection. Fuzzy ANP is used in the criteria and alternative assessment stages, obtains weights from each of the criterion, then calculations with TOPSIS are used to rank the supplier alternatives. This study aims to determine a permanent supplier for PT. X based on calculations using Fuzzy ANP and TOPSIS. The research data are obtained from interviews and questionnaires filled out by the factory manager. The results of this study show that there are 6 criterion that are taken into consideration within supplier selection, each is followed by the priority vectors: quality (0.302), shipment (0.183), production capacity (0.130), product repair service (0.091), supplier profile (0.052), and price (0.242). The results also show that PT. A is the most optimum packaging boxes supplier for PT. X.